Behavioral intention in using Islamic coins: exploring the acceptance of dinar and dirham among Muslim in Kelantan / Mohd Arif Zulkfli - Zulkfli, Mohd Arif (2013)
The main objective of this research is to discover the relationship between performance expectancy, perceived credibility and religiosity with behavioral intention in using Islamic Coins. The additional objectives are to determine which of the factor has greater effect on acceptance of Dinar and Dirham among Muslims in Kelantan. The main determinant of this research which factor the most influence towards acceptance of Dinar and Dirham among Muslims in Kelantan. The dependent variable of this study is behavioral intention to use Islamic coins which is has a significant relationship by independent variable consists of perceived credibility, performance expectancy and religiosity. The data for this research was obtained from survey. A set of questionnaires has been distributed among the Muslims and done to 150 of randomly selected respondents around Rantau Panjang, Tanah Merah and Jeli, Kelantan. Basically, the questions of survey based on the Muslims' perception and their acceptance towards the significant role in practicing Dinar and Dirham in daily transactions. The data were analyzed using IBM SPSS Version 16 through the frequency analysis, reliability analysis, descriptive analysis, correlation of coefficient and regression analysis.